TRANSFORMASI SDM ISLAMI DALAM MEWUJUDKAN PEMBANGUNAN MANUSIA BERKUALITAS - Ma'atus Sholikha, Lely Nur; Ni'mati Rahmatika, Arivatu; Widyahningsih, Bekti (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Abstract: Human resource (HR) transformation based on Islamic values is key to achieving overall quality human development. This article examines the role of Islamic education and character development in shaping superior human resources, both intellectually and morally, with a strong sense of faith. This approach is crucial for addressing the challenges of globalization and the Fourth Industrial Revolution while maintaining Islamic identity. Using qualitative descriptive methods, this article outlines a strategy for transforming Islamic HR, encompassing spiritual, moral, intellectual, and social aspects as the primary capital for national development. Keywords: Human Resource Transformation, Islamic Education, Quality Human Development